Social subsidies and marketization: The role of gender and skill - Robert Duval-Hernández; Lei Fang; Liwa Rachel Ngai (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper decomposes the differences in aggregate market hours between US and Europe across gender-skill groups and finds that low-skilled women are the biggest contributors to aggregate differences, with the exception of Nordic countries. We develop a model to account for the gender-skill differences in market hours across countries. Taxes, which reduce market hours in favor of leisure and home production, explain a substantial fraction of the differences in hours for Southern and Central European countries. Subsidized family care, which reduces home hours of women in favor of market hours, explains the different pattern of hours in Nordic countries. Low-skilled women are more responsive to policy because of their comparative advantage in producing home services and the corresponding market substitutes.
Keywords: E24; E62; J22; 330; Cross-country Differences in Market Hours; Home Production; Subsidies on Family Care